Bastards of Utopia - Razsa, Maple; Velez, Pacho (United States, 2010)
Three Croatian activists struggle to change the world. As children, they lived through the violent collapse of Yugoslavia. But now, amid the aftershocks of socialism's failure, they fight in their own way for a new leftism. In the middle of the struggle, a skeptical American is won over by their cause. The activists, whether clashing with police or squatting in an old factory, risk everything to live their politics.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films